PERSEPSI PELAYANAN DAN KINERJA PETUGAS POSYANDU TERHADAP TINGKAT KEPUASAN IBU BALITA DI POSYANDU DESA PREMBUN KECAMATAN TAMBAK KABUPATEN BANYUMAS - Purwanti, Sugi; ., Haryati; ., Asrin (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2013)
The level of satisfaction is a function of the difference between perceived performance to expected. The new patients will be satisfied if the performance of health services which is obtained equal or exceed his expectations. In contrast, patient dissatisfaction or disappointment feelings will appear when the performance of the health service was not obtained in accordance with expectations. Customer satisfaction is determined by the customer's perception of the product performance or service to meet customer expectations. Customers are satisfied when expectations are fulfilled or will be very satisfied if the customer's expectations are exceeded. Knowing the relationship between perception of service and performance of health care post officer with satisfaction of toddlers mother in Prembun Village Health Care Post Tambak Subdistrict Banyumas Regency in 2013. This study was an analytic study with cross sectional approach. The population in this study as many as 196 toddlers mother. The sampling use simple random sampling technique with the amount of sample were 66 toddlers mother. Majority of service perception percentage there is in the enough category with enough satisfaction of toddlers mother as many as 19 peoples (63,33%). Majority of health care post officer performance percentage there is in the enough category with enough satisfaction of toddlers mother as many as 25 peoples (86,21%). The calculations show that  value is 0,000 < 0,05. So, there is a relationship  between perception of service and performance of health care post officer with satisfaction of toddlers mother. There is a relationship  between perception of service and performance of health care post officer with satisfaction of toddlers mother. Midwives should be more intesified the health care post activities to motivate the cadres to be more active. Keywords       : Performance, Services perception,  Level of  satisfaction